Coating process of plastic-free paper
By adding sodium carbonate to the first coating solution in a plastic-free paper coating process to neutralize the acidity and controlling the heating temperature, the problem of decreasing adhesion in the existing process is solved, and better adhesion and adhesion are achieved Spend.
Patent Information
- Application Number
- CN202411860017.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-02-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the existing plastic-free coating process, the acetic acid solution of chitosan causes acidity of the coating solution, affects the adhesion of sodium alginate, and improper heating temperature leads to a reduction in adhesion.
By adding sodium carbonate to the first coating solution to neutralize the acidity, the viscosity of the sodium alginate is maintained in a stable state, and the heating temperature of the first coating is controlled to be between 45°C and 55°C to improve the adhesiveness.
It effectively improves the viscosity and adhesion of the coating liquid, ensuring good adhesion and degradation performance of the coating layer to the base paper.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coating technology for plastic-free paper, in particular to a coating technology for plastic-free paper. Background Art
[0002] Plastic-free coated paper is an environmentally friendly paper that uses a green plastic-free coating on the surface of the paper. It has high barrier and hydrophobic properties and can replace plastic film to make paper bags and other packaging materials. Plastic-free coated paper can be recycled after being discarded, which helps reduce resource consumption, reduce greenhouse gas emissions, and achieve sustainable development.
[0003] The plastic-free paper coating process with publication number CN116397457A adopts hard self-crosslinking acrylic emulsion, soft self-crosslinking acrylic emulsion, hexenyl bisstearamide, acrylic ester leveling agent, polyol, plasticizer, tung oil, chitosan acetic acid solution and sodium alginate aqueous solution to prepare plastic-free coating and apply it on base paper. The plastic-free coating made of the above raw materials is non-toxic. The prepared coating layer can be quickly attached to the base paper after being coated on the base paper, and the plastic-free paper can be quickly degraded, reducing pollution to the environment and having good environmental protection.
[0004] However, research has shown that the above-mentioned plastic-free paper coating process still has the following defects:
[0005] The above patent uses an acetic acid solution of chitosan, which is an acidic solution. This will cause the coating liquid to be acidic. At the same time, sodium alginate will affect the charge state of the sodium alginate molecules under acidic conditions, causing part of the positive charge to be converted into negative charge, so that the overall number of negative charges is greater than the positive charge. The excess negative charges repel each other, thereby reducing the interaction force between molecules, thereby reducing the viscosity of the solution and reducing the adhesion of sodium alginate. This will cause the adhesion of the coating liquid to the base paper to become worse. At the same time, the temperature of the first heating is greater than the temperature of the second heating. Too high a temperature will make the surface of the first coating film too dry and the viscosity will be reduced, thereby reducing the viscosity of the first coating paper and the second coating liquid. Therefore, it is necessary to optimize the coating process of a plastic-free paper through technological innovation and design optimization. Summary of the invention
[0006] In order to solve the above problems, the embodiment of the present application provides a coating process for plastic-free paper. By adding sodium carbonate to the first coating liquid, the acidity of the first coating liquid can be neutralized, so that the first coating liquid is neutral, and the viscosity of the sodium alginate can be maintained in a stable and good state, which is convenient for improving the viscosity of the coating liquid. At the same time, the heating temperature of the first coating is set at 45°C-55°C to ensure that the adsorption of the coating material on the surface of the first coated paper is in a good bonding state, which is convenient for bonding with the coating liquid of the second coating, and can effectively improve the adhesion. Ensuring that the heating and drying temperatures do not exceed 80°C can avoid a decrease in the adhesion between the materials.
[0007] The technical solution adopted by the embodiment of the present application to solve the technical problem is:
[0008] A coating process for plastic-free paper, comprising:
[0009] Step 1: According to the weight ratio, 100 parts of hard self-crosslinking acrylic emulsion, 5 parts of hexenyl bisstearamide, 8 parts of acrylic leveling agent, 18 parts of polyol and 6 parts of plasticizer are stirred and mixed to obtain a first ratio liquid;
[0010] Adding acrylic leveling agents can not only promote the flow and leveling of the coating, but also will not affect the interlayer adhesion of the coating, and also has a defoaming effect.
[0011] Step 2: Add 28 parts of chitosan acetic acid solution and 28 parts of sodium alginate aqueous solution to the first ratio liquid, place the first ratio liquid in a heating box and heat it to a specified temperature, stir it with a stirrer, and then place it in a heating furnace to heat it;
[0012] Chitosan has multiple physiological functions such as biodegradability, biocompatibility, non-toxicity, antibacterial, anti-cancer, lipid-lowering, and immune enhancement. It is generally dissolved in an acid solution when used. Sodium alginate aqueous solution has stability, solubility, viscosity, and safety.
[0013] Step 3: adding 14 parts of sodium carbonate into the first proportioning liquid and stirring and mixing to obtain a first coating liquid;
[0014] Step 4: 100 parts of soft self-crosslinking acrylic emulsion, 10 parts of tung oil, 14 parts of polyol, 5 parts of acrylic leveling agent and 5 parts of plasticizer are stirred and mixed to obtain a second ratio liquid;
[0015] A protective film is formed on the surface of tung oil, which is airtight and thus has a waterproof and anti-corrosion effect. It can also make the paper softer and more resilient.
[0016] Step 5: Place the second ratio liquid in a heating box and heat it to a specified temperature, then stir it, and then place it in a heating furnace to heat it to obtain a second coating liquid;
[0017] Step 6: coating the first coating liquid on the upper surface of the base paper for the first time to obtain the first coated paper, and placing the first coated paper in a drying box for the first drying;
[0018] Step 7: coating the first coated paper after the first drying with a second coating liquid to obtain a second coated paper, and placing the second coated paper in a second drying box for drying;
[0019] Step 8: Place the dried second coated paper into a drying cylinder for drying and ironing.
[0020] In a possible implementation, when the first proportioning liquid in step 1 is stirred, the stirring time needs to be ensured to be 30 minutes, and the stirring needs to be firstly stirred clockwise for 10 minutes and then stirred counterclockwise for 15 minutes.
[0021] Stirring in the opposite direction helps to break the intermolecular forces and facilitate the molecules to recombine with each other.
[0022] In one possible implementation, in step 2, the acetic acid solution of chitosan is first added to the first ratio liquid, and then the sodium alginate aqueous solution is added after waiting for 5 minutes, and then the first ratio liquid is heated to a temperature of 70°C, stirred, and placed in a heating furnace with a temperature of 70°C and a heating time of 65 minutes.
[0023] In one possible implementation, the reaction of sodium carbonate and acetic acid in step three is exothermic, and sodium acetate needs to be added to the first proportioning liquid in multiple times. When the solution temperature is higher than 60°C, stirring is stopped, and sodium acetate is added and stirred again when the solution drops to 40°C. The above steps are repeated until all sodium acetate is added to the first proportioning liquid.
[0024] Sodium carbonate and acetic acid can undergo a neutralization reaction, and the reaction equation is as follows: Na2CO3+2CH3COOH=2CH3COONa+CO2+H20. The substance produced after the reaction is non-toxic and harmless, and can neutralize the acetic acid solution, making the first coating liquid neutral, which can maintain the viscosity of sodium alginate in a stable and good state, and is convenient for improving the viscosity of the coating liquid.
[0025] In a possible implementation, the stirring time in step 4 is 20 minutes, and the stirring is performed at a low speed of 60 r / min for the first 10 minutes, and then at a high speed of 120 r / min for 10 minutes.
[0026] The second proportioning liquid is first stirred at a low speed to make it more fluid, and then it is convenient to stir it at a high speed.
[0027] In one possible implementation, in step five, the second proportioning liquid needs to be heated to 50°C with the help of a heating box, stirred, and then the heating furnace is heated to 50°C, and the second proportioning liquid is placed in the heating furnace with the help of a tool, and heated at 50°C for 30 minutes, and then the temperature of the heating furnace is adjusted to 70°C and heated for 20 minutes.
[0028] The second ratio liquid has the best solubility at 50°C, which facilitates the mutual combination of molecules.
[0029] In a possible implementation, in step six, the base paper is coated three times using a brush, and it is coated again after waiting for 10 minutes after each coating. The temperature of the drying box is first set to 10°C, and the first coated paper is placed in the drying box. Then the temperature of the drying box is increased by 15°C every 10 minutes, and the drying time is 50 minutes.
[0030] A slow temperature rise can avoid incomplete drying due to a rapid temperature rise.
[0031] In a possible implementation, the temperature of the drying box in step seven is set to 50° C. and the temperature remains constant. After drying for 20 minutes, the heating furnace is turned off, and the second coated paper is allowed to slowly cool to room temperature along with the drying box before being taken out of the drying box.
[0032] The second coated paper is slowly cooled to room temperature along with the drying oven to avoid direct contact between the second coated paper and room temperature, which may cause cracks due to a large temperature difference.
[0033] In a possible implementation, the total thickness of the first coating liquid coated on the base paper is 0.15 mm-0.2 mm, and the total thickness of the second coating liquid coated on the top layer of the first coated paper is 0.1-0.15 mm. The thickness in this range can fit the base paper well.
[0034] In a possible implementation, the temperature in the drying cylinder in step eight is 60° C. After drying for 30 minutes, the second coated paper needs to be taken out, brushed with a layer of clean water using a brush, and then put into the drying cylinder to dry for 60 minutes.
[0035] The viscosity of sodium alginate will decrease when the temperature exceeds 80℃, so it is necessary to ensure that the heating temperature and drying temperature are below 80℃. Brushing with clean water can prevent the coating layer from drying and cracking during drying.
[0036] In summary, the present invention includes at least one of the following beneficial technical effects:
[0037] 1. By adding sodium carbonate to the first coating liquid, the acidity of the first coating liquid can be neutralized, making the first coating liquid neutral, so that the number of positive charges and negative charges in the solution can be kept equal, the positive charges and negative charges attract each other, and then the intermolecular force is increased, so that the viscosity of sodium alginate can be maintained in a stable and good state, which is convenient for improving the viscosity of the coating liquid.
[0038] 2. At the same time, setting the heating temperature of the first coating at 45°C-55°C can ensure that the coating material on the surface of the first coated paper will not become very dry, so that its adsorption is in a better state, which is convenient for bonding with the coating liquid of the second coating, and can effectively improve the adhesion. DETAILED DESCRIPTION
[0039] The technical solution of the present invention will be described clearly and completely below. In addition, the forms of the various structures recorded in the following embodiments are merely illustrative. The instrument placement rack involved in the present invention is not limited to the various structures recorded in the following embodiments. All other embodiments obtained by ordinary technicians in this field without making creative work belong to the scope of protection of the present invention.
[0040] Example:
[0041] A coating process for plastic-free paper, comprising:
[0042] Step 1: According to the weight ratio, 100 parts of hard self-crosslinking acrylic emulsion, 5 parts of hexenyl bisstearamide, 8 parts of acrylic leveling agent, 18 parts of polyol and 6 parts of plasticizer are stirred and mixed to obtain a first ratio liquid;
[0043] Adding acrylic leveling agents can not only promote the flow and leveling of the coating, but also will not affect the interlayer adhesion of the coating, and also has a defoaming effect.
[0044] Step 2: Add 28 parts of chitosan acetic acid solution and 28 parts of sodium alginate aqueous solution to the first ratio liquid, place the first ratio liquid in a heating box and heat it to a specified temperature, stir it with a stirrer, and then place it in a heating furnace to heat it;
[0045] Chitosan has multiple physiological functions such as biodegradability, biocompatibility, non-toxicity, antibacterial, anti-cancer, lipid-lowering, and immune enhancement. It is generally dissolved in an acid solution when used. Sodium alginate aqueous solution has stability, solubility, viscosity, and safety.
[0046] Step 3: adding 14 parts of sodium carbonate into the first proportioning liquid and stirring and mixing to obtain a first coating liquid;
[0047] Step 4: 100 parts of soft self-crosslinking acrylic emulsion, 10 parts of tung oil, 14 parts of polyol, 5 parts of acrylic leveling agent and 5 parts of plasticizer are stirred and mixed to obtain a second ratio liquid;
[0048] A protective film is formed on the surface of tung oil, which is airtight and thus has a waterproof and anti-corrosion effect. It can also make the paper softer and more resilient.
[0049] Step 5: Place the second ratio liquid in a heating box and heat it to a specified temperature, then stir it, and then place it in a heating furnace to heat it to obtain a second coating liquid;
[0050] Step 6: coating the first coating liquid on the upper surface of the base paper for the first time to obtain the first coated paper, and placing the first coated paper in a drying box for the first drying;
[0051] Step 7: coating the first coated paper after the first drying with a second coating liquid to obtain a second coated paper, and placing the second coated paper in a second drying box for drying;
[0052] Step 8: Place the dried second coated paper into a drying cylinder for drying and ironing.
[0053] To ensure that the first ratio liquid has high adhesion, further, when stirring the first ratio liquid in step one, it is necessary to ensure that the stirring time is 30 minutes, and the stirring needs to be firstly stirred clockwise for 10 minutes and then stirred counterclockwise for 15 minutes.
[0054] Stirring in the opposite direction helps to break the intermolecular forces and facilitate the molecules to recombine with each other.
[0055] Furthermore, in step 2, the acetic acid solution of chitosan is first added to the first ratio liquid, and then the sodium alginate aqueous solution is added after waiting for 5 minutes, and then the first ratio liquid is heated to a temperature of 70°C, stirred, and then placed in a heating furnace, the temperature of the heating furnace is 70°C, and the heating time is 65 minutes.
[0056] The first ratio liquid is acidic, which will cause the viscosity of sodium alginate to decrease, and then cause the viscosity of the first ratio liquid to decrease, which may cause the first coating liquid to stick to the base paper and not be tight. Furthermore, the reaction of sodium carbonate and acetic acid in step three will release heat, and sodium acetate needs to be added to the first ratio liquid in multiple times. When the solution temperature is higher than 60°C, stop stirring, wait until the solution drops to 40°C, then add sodium acetate and stir, and repeat the above steps until all sodium acetate is added to the first ratio liquid.
[0057] Sodium carbonate and acetic acid can undergo a neutralization reaction, and the reaction equation is as follows: Na2CO3+2CH3COOH=2CH3COONa+CO2+H20. The substance produced after the reaction is non-toxic and harmless, and can neutralize the acetic acid solution, making the first coating liquid neutral, which can maintain the viscosity of sodium alginate in a stable and good state, and is convenient for improving the viscosity of the coating liquid.
[0058] Furthermore, the stirring time in step 4 is 20 minutes, and the stirring is performed at a low speed of 60 r / min for the first 10 minutes, and then at a high speed of 120 r / min for 10 minutes.
[0059] The second proportioning liquid is first stirred at a low speed to make it more fluid, and then it is convenient to stir it at a high speed.
[0060] Furthermore, in step five, the second proportioning liquid needs to be heated to 50°C with the help of a heating box, stirred, and then the heating furnace is heated to 50°C, and the second proportioning liquid is placed in the heating furnace with the help of a tool, first maintained at 50°C for 30 minutes, and then the temperature of the heating furnace is adjusted to 70°C and heated for 20 minutes.
[0061] The second ratio liquid has the best solubility at 50°C, which facilitates the mutual combination of molecules.
[0062] Furthermore, in step six, the base paper is coated three times using a brush, and it is coated again after waiting for 10 minutes after each coating. The temperature of the drying box is first set to 10°C, and the first coated paper is placed in the drying box. Then the temperature of the drying box is increased by 15°C every 10 minutes, and the drying time is 50 minutes.
[0063] A slow temperature rise can avoid incomplete drying due to a rapid temperature rise.
[0064] Furthermore, in step seven, the temperature of the drying box is set to 50° C. and the temperature remains constant. After drying for 20 minutes, the heating furnace is turned off, and the second coated paper is allowed to slowly cool to room temperature along with the drying box before being taken out of the drying box.
[0065] The second coated paper is slowly cooled to room temperature along with the drying oven to avoid direct contact between the second coated paper and room temperature, which may cause cracks due to a large temperature difference.
[0066] Furthermore, the total thickness of the first coating liquid coated on the base paper is 0.15 mm-0.2 mm, and the total thickness of the second coating liquid coated on the top layer of the first coated paper is 0.1-0.15 mm. The thickness in this range can fit the base paper well.
[0067] Furthermore, in step eight, the temperature in the drying cylinder is 60° C. After drying for 30 minutes, the second coated paper needs to be taken out, brushed with a layer of clean water using a brush, and then put into the drying cylinder for drying for 60 minutes.
[0068] The viscosity of sodium alginate will decrease when the temperature exceeds 80℃, so it is necessary to ensure that the heating temperature and drying temperature are below 80℃. Brushing with clean water can prevent the coating layer from drying and cracking during drying.
[0069] Comparative Example:
[0070] The operation steps of Comparative Example 1 are the same as those of Example 1, except that sodium carbonate is not added into the first coating liquid when the first coating liquid is prepared.
[0071] The operation steps of Comparative Example 2 are the same as those of Comparative Example 1, except that the temperature of the heating furnace is set to 65° C.-75° C. when heating the first coated paper.
[0072] The following are the test results of the finished products of Example, Comparative Example 1 and Comparative Example 2;
[0073]
[0074] From the test results in the above table, we can see that:
[0075] The viscosity of the finished product after being manufactured according to the operating steps of the embodiment is 29 Pa·s, the viscosity of the finished product after being manufactured according to the operating steps of the comparative example 1 is 27 Pa·s, and the adhesiveness of the finished product after being manufactured according to the operating steps of the comparative example 2 is 25 Pa·s. By comparing the embodiment and the comparative example 1, it can be seen that by ensuring that the heating temperature of the first coating paper is consistent and only the pH value is changed, the acidity of the first coating liquid can be neutralized by adding sodium carbonate to the first coating liquid, so that the first coating liquid is neutral, so that the number of positive charges and negative charges in the solution can be kept equal, the positive charges and negative charges attract each other, and then the intermolecular force is increased, so that The viscosity of sodium alginate is maintained in a stable and good state, which is convenient for improving the viscosity of the coating liquid. The viscosity of the embodiment is greater than that of the comparative example 1. At the same time, by comparing the comparative example 1 and the comparative example 2, it can be seen that by ensuring the consistency of the pH value, only changing the heating temperature of the first coating paper, and making the heating temperature of the first coating at 45°C-55°C, it can be ensured that the coating material on the surface of the first coating paper will not become very dry, so that its adsorption is in a good state, which is convenient for bonding with the coating liquid of the second coating, and can effectively improve the adhesion. The viscosity of the comparative example 1 is greater than that of the comparative example 2. It can be seen that the production effect according to the operating steps of the embodiment is the best.
[0076] Finally, it should be noted that: Obviously, the above embodiments are only examples for clearly explaining the present invention, and are not intended to limit the implementation methods. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from this are still within the scope of protection of the present invention.
Claims
1. A coating process for plastic-free paper, characterized in that: The following steps are involved: Step 1: According to the weight ratio, 100 parts of hard self-crosslinking acrylic emulsion, 5 parts of hexenyl bisstearamide, 8 parts of acrylic leveling agent, 18 parts of polyol and 6 parts of plasticizer are stirred and mixed to obtain a first ratio liquid; Step 2: Add 28 parts of chitosan acetic acid solution and 28 parts of sodium alginate aqueous solution to the first ratio liquid, place the first ratio liquid in a heating box and heat it to a specified temperature, stir it with a stirrer, and then place it in a heating furnace to heat it; Step 3: adding 14 parts of sodium carbonate into the first proportioning liquid and stirring and mixing to obtain a first coating liquid; Step 4: 100 parts of soft self-crosslinking acrylic emulsion, 10 parts of tung oil, 14 parts of polyol, 5 parts of acrylic leveling agent and 5 parts of plasticizer are stirred and mixed to obtain a second ratio liquid; Step 5: Place the second ratio liquid in a heating box and heat it to a specified temperature, then stir it, and then place it in a heating furnace to heat it to obtain a second coating liquid; Step 6: coating the first coating liquid on the upper surface of the base paper for the first time to obtain the first coated paper, and placing the first coated paper in a drying box for the first drying; Step 7: coating the first coated paper after the first drying with a second coating liquid to obtain a second coated paper, and placing the second coated paper in a second drying box for drying; Step 8: Place the dried second coated paper into a drying cylinder for drying and ironing.
2. A coating process for plastic-free paper according to claim 1, characterized in that: When stirring the first proportioning liquid in step 1, the stirring time needs to be ensured to be 30 minutes, and the stirring needs to be first stirred clockwise for 10 minutes and then stirred counterclockwise for 15 minutes.
3. A coating process for plastic-free paper according to claim 1, characterized in that: In step 2, the acetic acid solution of chitosan is first added to the first ratio liquid, and then the sodium alginate aqueous solution is added after waiting for 5 minutes. The first ratio liquid is then heated to a temperature of 70°C, stirred, and placed in a heating furnace with a temperature of 70°C and a heating time of 65 minutes.
4. A coating process for plastic-free paper according to claim 1, characterized in that: In step 3, the reaction of sodium carbonate and acetic acid will release heat, and sodium acetate needs to be added to the first proportioning liquid in multiple times. When the solution temperature is higher than 60°C, stop stirring, wait until the solution drops to 40°C, then add sodium acetate and stir, and repeat the above steps until all sodium acetate is added to the first proportioning liquid.
5. A coating process for plastic-free paper according to claim 1, characterized in that: The stirring time in step 4 is 20 minutes. The first 10 minutes of stirring are stirred at a low speed of 60 r / min, and then stirred at a high speed of 120 r / min for 10 minutes.
6. A coating process for plastic-free paper according to claim 1, characterized in that; In step five, the second proportioning liquid needs to be heated to 50°C with the help of a heating box, stirred, and then the heating furnace is heated to 50°C. The second proportioning liquid is placed in the heating furnace with the help of a tool, and heated at 50°C for 30 minutes. Then the temperature of the heating furnace is adjusted to 70°C and heated for 20 minutes.
7. A coating process for plastic-free paper according to claim 1, characterized in that: In step six, the base paper is coated three times using a brush, and it is coated again after waiting for 10 minutes after each coating. The temperature of the drying box is first set to 10°C, and the first coated paper is placed in the drying box. Then the temperature of the drying box is increased by 15°C every 10 minutes, and the drying time is 50 minutes.
8. A coating process for plastic-free paper according to claim 6, characterized in that: In step 7, the temperature of the drying box is set to 50° C. and the temperature remains constant. After drying for 20 minutes, the heating furnace is turned off, and the second coated paper is allowed to slowly cool to room temperature along with the drying box before being taken out of the drying box.
9. A coating process for plastic-free paper according to claim 7, characterized in that: The total thickness of the first coating liquid coated on the base paper is 0.15 mm-0.2 mm, and the total thickness of the second coating liquid coated on the top layer of the first coated paper is 0.1-0.15 mm.
10. A coating process for plastic-free paper according to claim 4, characterized in that: In step eight, the temperature in the drying cylinder is 60° C. After drying for 30 minutes, the second coated paper needs to be taken out, brushed with a layer of clean water using a brush, and then put into the drying cylinder for drying for 60 minutes.
Citation Information
Patent Citations
Plastic-free paper coating process
CN116397457A